Breathable Lignin Nanoparticles as Reversible Gas Swellable Nanoreactors. Issue 7 (7th December 2022) - Moreno, Adrian; Delgado‐Lijarcio, Javier; Ronda, Juan C.; Cádiz, Virginia; Galià, Marina; Sipponen, Mika H.; Lligadas, Gerard
Abstract: The design of stimuli‐responsive lignin nanoparticles (LNPs) for advanced applications has hitherto been limited to the preparation of lignin‐grafted polymers in which usually the lignin content is low (<25 wt.%) and its role is debatable. Here, the preparation of O2 ‐responsive LNPs exceeding 75 wt.% in lignin content is shown. Softwood Kraft lignin (SKL) is coprecipitated with a modified SKL fluorinated oleic acid ester (SKL‐OlF) to form colloidal stable hybrid LNPs (hy‐LNPs). The hy‐LNPs with a SKL‐OlF content ranging from 10 to 50 wt.% demonstrated a reversible swelling behavior upon O2 /N2 bubbling, increasing their size – ≈35% by volume – and changing their morphology from spherical to core‐shell. Exposition of hy‐LNPs to O2 bubbling promotes a polarity change on lignin‐fluorinated oleic chains, and consequently their migration from the inner part to the surface of the particle, which not only increases the particle size but also endows hy‐LNPs with enhanced stability under harsh conditions (pH < 2.5) by the hydration barrier effect. Furthermore, it is also demonstrated that these new stimuli‐responsive particles as gas tunable nanoreactors for the synthesis of gold nanoparticles. Combining a straightforward preparation with their enhanced stability and responsiveness to O2 gas these new LNPs pave the way for the next generation of smart lignin‐based nanomaterials. Abstract : Raw softwood Kraft lignin (SKL) is coprecipitated with a modified SKL fluorinated oleic acid ester (SKL‐OlF) to form colloidal stable hybrid LNPs (hy‐LNPs). These new hy‐LNPs demonstrated a reversible swelling behavior upon O2 /N2 bubbling, increasing their size, changing their morphology, and improving their stability in acidic conditions owing to the effect provided by the O2 ‐induced migration of fluorinated oleic acid chains to the surface of the particles. In addition, these new stimuli‐responsive particles are also demonstrated as gas tunable nanoreactors for the synthesis of gold nanoparticles.